UPAYA MITIGASI BENCANA GERAKAN TANAH DALAM PERSPEKTIF ISLAM (Studi Kasus Penambangan Pasir Ilegal Di Kecamatan Bangsal Kabupaten Mojokerto) - Fadlilah, Sulfatul (El-Hayah : Jurnal Biologi, 2014)
Ilegal sand mining after days was not restrained, and it caused land movement in every dikes of Brantas river. In Alquran, (Ar Rum:30) said that the disaster is made by the human, they have to chance the bad behavior/habits if they wants the disaster will not happen. This research has puspose for knowing the subjects of ilegal sand mining and how far the impact of sand mining. The methode of the researchÂ  is quantitative and for the collect data are introgation, observation, and documentation to get more information about ilegal sand mining. In UU No 23 Year 1997, that every body have to keep environment to ward off the disaster. The government has to take any strategic ways to move the ilegal sand mining practice